Proving parentage by scientific methods in Algerian law and its problems - امزيان راضية (Journal of Human Sciences, 2022)
This research aims to clarify the importance of scientific methods that can be depend on it to prove parentage according to Article 40/2 of the Algerian Family Code, and to know the extent to which its efficacy in proof is estimated. Because today we do not rely on the classic evidence To prove the lineage. In this research, we relied on many scientific methods Like the legal approach By addressing various laws related to the family. and we also relied on the descriptive-analytical approach. because of the results they give that are almost one hundred percent real, , we reached many results, the most important of which is that these scientific methods have proven their actual efficacy in proving the lineage. because of the results they give that are almost one hundred percent real, This is in order to preserve the identification of children in the event of their loss or mixing in hospitals, and even to establish the parentage of unknown children we also presented a set of recommendations and scientific methodological suggestions that may contribute to enriching this topic from a legal point of view.